Update on the running time prediction formula
To evaluate the formula mathematically, I first converted the 5k time to average velocity, then divided the longer distances by the appropriate percentage of that velocity (95%-10k, 90%- 1/2 marathon, and 85% for marathon) to determine predicted velocity for those events. I compared these predicted values with actual performance values.